Social representations of Typhoon Haiyan/Yolanda in Filipino and American news media groups coverage - Ramos, Rogene; Reston, Romel (2015)
This study aimed to determine how Typhoon Yolanda or Haiyan was portrayed in the American and Filipino media group. The way disasters are portrayed in the media serves as a map for humans to make a complex phenomenon more comprehensible. With this, the media plays an important role in the transformation of scientific knowledge to laypeople. In this study, the Social Representation Theory (SRT) was used to compare how the Filipino and American media groups portrayed Typhoon Haiyan/Yolanda. Focusing on three broadsheets in each media group, the articles were analyzed using thematic analysis. The results revealed that there were more similarities than differences found in both media groups. The social representations that the news media groups shared were Typhoon Haiyan/Yolanda as a monster, a tragedy, and a natural calamity. This similarity in social representations may be due to the training of Filipino journalists in the Western style of journalism. However, the two media groups differed in representing the typhoon as a social or political crisis and may have a gap in knowledge of the political and social situations in the country. SRT may be used to explore how the media may influence the cognition and effect of the audience they have reached.